DEVELOPMENT OF IPS-BASED TEACHING MATERIALS FLIPBOOK CLASS VI MATERIAL ON GEOGRAPHIC, SOCIAL AND CULTURAL CONDITIONS OF ASEAN COUNTRIES - Wahyu Setiyono; Gigih Winandika (PROCEEDING AL GHAZALI International Conference, 2023)
Technology is currently developing rapidly. One can quickly access knowledge anywhere, anytime, using a device. Developments also occurred in the field of education. Technology is developing quickly, and it can be leveraged in the classroom to improve student learning. Geographical material as well as the social and cultural conditions of ASEAN countries can be utilized effectively through the development of class VI social studies teaching resources flipbook. The validation results of media experts are included in the very suitable criteria, and the results of material expert verification are also included in the very suitable criteria. The student response was categorized as very effective, and the teacher's response was categorized as very appropriate. Therefore, it is very suitable for use in learning to develop teaching resources for class VI social studies flipbook which includes geographical material as well as the social and cultural conditions of the ASEAN nation. The efficacy of these teaching materials in learning can improve student learning outcomes. Based on the findings of the t test carried out at a significance level of 0.00 less than the threshold of 0.05, it can be concluded that the use of social studies teaching material construction is based on flipbook for class VI which focuses on geography and social culture of ASEAN countries is useful in improving student learning outcomes. Using Canva, a project is created during the development stage. At the implementation stage, product trials were carried out by material experts with a validity level of 85.31% and media experts with a validity level of 93.75% and very good credentials. The final stage is evaluation, namely conducting product trials with very good qualifications and a validity level of 81.25%. Overall, the findings of this study show how suitable the product created is for use during the educational process.